2022
DOI: 10.1177/23337214221122523
|View full text |Cite
|
Sign up to set email alerts
|

Pioneering COVID-19 Pandemic Partnerships: Federally Qualified Health Centers and Geriatric Workforce Enhancement Programs Work Together to Care for Diverse Underserved Older Adults

Abstract: Background: The COVID-19 pandemic disproportionately affected populations served by Federally Qualified Health Centers (FQHCs), with high morbidity and mortality rates in ethnic minority older adults. In response to this pandemic, academic geriatric medicine teams through federally funded Geriatric Workforce Enhancement Program (GWEP) with FQHC partnership implemented new initiatives to improve the care for vulnerable older adults. Objectives: To describe how four FQHC/GWEP teams collaborated in caring for div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Lastly, a call to action is needed to develop and sustain an infrastructure grounded in collaborative research and community engagement to respond to low rates of ACP documentation for the people living with ADRD [ 13 ]. Greater awareness of the potential and likely harm from the lack of ACP documentation will likely play a pivotal role in training a future geriatrics workforce to provide both telehealth and in-person primary care services [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, a call to action is needed to develop and sustain an infrastructure grounded in collaborative research and community engagement to respond to low rates of ACP documentation for the people living with ADRD [ 13 ]. Greater awareness of the potential and likely harm from the lack of ACP documentation will likely play a pivotal role in training a future geriatrics workforce to provide both telehealth and in-person primary care services [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a provider shortage area, workforce training is a realistic priority strategy to enhance quality of care outcomes [ 34 ]. The Age-Friendly Health System 4M framework (What Matters, Mobility, Medication, Mentation) is an easily adoptable toolkit for evaluating the quality of care and a workforce education competency tool for use across diverse local healthcare systems and care settings [ 33 , 34 , 35 ]. In the recent quantitative analysis of reviewing EHRs to measure the rate of documenting 4M elements in one Nevada health system adopting the 4M framework in its primary telehealth services, What Matters (62.2%) was the most common 4M element to be documented, and within the components of What Matters, ACP discussion was the most commonly (29.0%) documented [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telehealth holds great promise for enhancing primary care access among older and vulnerable adults especially if they need transportation support ( Gibbs et al, 2022 ). Studies have shown that telehealth utilization is associated with better outcomes in chronic disease management and reduced healthcare disparities across racial and ethnic boundaries ( Bose et al, 2022 ; Dryden et al, 2022 ; McQuown et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%